FAKTOR YANG MEMPENGARUHI RELIABILITAS LAPORAN KEUANGAN PEMERINTAH DAERAH - Paderry, Paderry (JURNAL FAIRNESS, 2016)
This study aims to examine and obtain empirical evidence about factors that affect the reliability of local government financial reporting. This research is motivated by the fact that the  local government financial reporting should provide information on reliable in assessing accountability and decision making of various parties.  Variables that will be tested in this study is the quality of human resources, utilization of information technology, accounting internal controls, and organizational commitment (as an independent variable) against the reliability of local government financial reporting (as the dependent variable).The data in this study is the primary data obtained from questionnaires distributed directly to the respondents. Data collected from 66 respondents who are local government financial reporting staff in the Rejang Lebong district. The hypothesis in this study were tested using t test and f test.The results of this study is test showed that the quality of human resources, the utilization of information technology, internal accounting controls, and organizational commitment significantly influence the reliability of local government  financial reporting.